2014
DOI: 10.4236/ajac.2014.58058
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Fenton Catalyst for the Efficient Removal of Azo Dyes in Water

Abstract: Heterogeneous Fenton/photo Fenton type processes using a Fe-exchanged zeolite of Y-type have been applied for the degradation of a model textile synthetic water based on Black B azodye. Research work has been directed to compare process efficiency and to establish their advantages over corresponding homogenous Fenton type processes. By optimizing the amount of reactants and process conditions, a complete decolorization of the effluent and a reduction greater than 80 per cent in the total organic carbon content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…9 and Table 3), it was confirmed that the reaction rate of heterogeneous oxidations was lower than that observed for the homogeneous ones, whereas the activation energy was higher, with the concomitant lower TOC conversion values. The results agree with those obtained by other authors [26], [54][55][56] and may be due to the reduced accessibility of H 2 O 2 to copper, as the active phase is supported on γ-Al 2 O 3 .…”
Section: Toc Reduction By Homogeneous Oxidationssupporting
confidence: 92%
“…9 and Table 3), it was confirmed that the reaction rate of heterogeneous oxidations was lower than that observed for the homogeneous ones, whereas the activation energy was higher, with the concomitant lower TOC conversion values. The results agree with those obtained by other authors [26], [54][55][56] and may be due to the reduced accessibility of H 2 O 2 to copper, as the active phase is supported on γ-Al 2 O 3 .…”
Section: Toc Reduction By Homogeneous Oxidationssupporting
confidence: 92%
“…The results in this study, therefore, suggest that methanol is a preferred solvent over water if the PODS reaction is to be carried out in a batch mode without flowing air. A trial was also conducted with a heterogeneous photo-Fenton catalyst (Fe 3+ ) supported on zeolite-Y (Fe/zeolite Y) which has been shown as an effective photo-catalyst for oxidation of organics at high concentration through rapid generation of hydroxyl radicals [20]. Fig.…”
Section: Solvent Requirement Of Podsmentioning
confidence: 99%
“…Adsorption mechanisms require a suitable adsorbent material with a high removal capacity [14]. Normally, the materials chosen for such applications are those with a high degree of porosity, high cationic exchange capacity (CEC), specific surface area, environmental capability, availability and cost-effectiveness [15,16]. Additionally, to be economically advantageous, the material must have low economic value.…”
Section: Introductionmentioning
confidence: 99%
“…Clinoptilolite is one of the predominant natural species of zeolites and has been successfully used for contaminant removal [15,44]. This mineral belongs to the heulandite group and comprises a two-dimensional channel system (a 10-ring system (0.31 nm × 0.75 nm), an 8-ring system (0.36 nm × 0.46 nm) and channels (0.28 nm × 0.47 nm) [45].…”
Section: Introductionmentioning
confidence: 99%